Extraction of Pelletierine from Punica granatum L.by Liquid Membrane Technique and Modelling - A. Al-Hemiri, Adel; M. Abed, Khalid; W. Al-Shahwany, Ayaad (Iraqi Journal of Chemical and Petroleum Engineering, 2012)
This work was conducted to study the extraction of pelletierine sulphate from Punica granatum L. roots by liquid membrane techniques. Pelletierine sulphate is used widely in medicine. The general behavior of extraction process indicates that pelletierine conversion increased with increasing the number of stages and the discs rotation speed but high rotation speed was not favored because of the increased risk of droplet formation during the operation. The pH of feed and acceptor solution was also important. The results exhibit that the highest pelletierine conversion was obtained when using two stages, (10 rpm) discs speed of stainless steel discs, (pH=9.5) of feed solution and (pH=2) of acceptor solution in n-decane. Assuming the existence of two thin reaction layers in the feed and stripping solutions, mathematical model was developed to describe the pelletierine transport. On the basic of the experimental data obtained under various conditions and the model proposed, it was found that the solute transfer into the liquid membrane is mainly diffusion-controlled.